The Resiliency of Islamic Boarding Schools in the Covid-19 Pandemic Era - Buchori, Imam; Junjunan, Mochammad Ilyas; Nawangsari, Ajeng Tita (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study focuses on the administrative leadership, financial oversight, and instructional practices of the boarding schools al-Amanah Junwangi, Manba'ul Hikam Putat, and Annur Penatarsewu, Sidoarjo. This study employed a quantitative approach and a case study methodology. Respondents who served as informants for the study included KH. Nurcholis Misbah from al-Amanah, KH. Muh. Salim Imron from Manba'ul Hikam, and KH. Anwar Ichsan from Annur. To give more pertinent supporting information, additional respondents were also included. The findings of this study include Islamic boarding schools applying various learning patterns, ranging from full online, hybrid class systems, to face-to-face by maintaining distance. Additionally, al-Amanah and Manba'ul Hikam were not as negatively impacted financially because the two boarding schools had sufficient